Quick-setting agent for pozzolanic material-containing cement, spray material, and sprayed concrete
Patent Information
- Application Number
- JP2023136574
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-03-07
AI Technical Summary
【0010】 本発明によれば、強度発現性及び急結性に優れ、六価クロム溶出を抑制できるポゾラン物質含有セメント用急結剤を提供することが出来る。
Smart Images

Figure 2025030890000001 
Figure 2025030890000002 
Figure 2025030890000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pozzolanic substance-containing cement quick-setting admixture, a spraying material, and a sprayed concrete. [Background technology]
[0002] Conventionally, in order to prevent the collapse of exposed natural ground such as in tunnel excavation, a method of spraying quick-setting concrete in which an accelerator is mixed into the concrete has been used. In this method, materials are measured and mixed in a measuring plant installed at the excavation site to prepare the shotcrete, which is then pumped and mixed with the accelerator pumped from the other side of the junction pipe, and sprayed onto the natural ground until a specified thickness is reached.
[0003] As quick-setting admixtures, there have been proposed a liquid quick-setting admixture comprising a combination of a fluoride-containing water-soluble aluminum complex obtained by the reaction of aluminum sulfate with hydrofluoric acid, aluminum hydroxide, and phosphorous acid and / or an organic acid salt thereof (see Patent Document 1); a concrete quick-setting admixture containing at least one selected from the group consisting of aluminum fluoride, an acidic or basic solution of aluminum, lithium silicate, and lithium aluminate (see Patent Document 2); and a liquid quick-setting admixture comprising a fluoride-containing water-soluble aluminum salt obtained by the reaction of aluminum sulfate with hydrofluoric acid, aluminum hydroxide, and lithium hydroxide, lithium carbonate, lithium sulfate, or the like (see Patent Document 3).
[0004] On the other hand, in recent years, there has been a demand to reduce the amount of cement used in order to reduce carbon dioxide emissions, and the use of by-products such as fly ash and silica fume has been considered. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2006-193388 A [Patent Document 2] JP 2001-130935 A [Patent Document 3] JP 2005-89276 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, pozzolanic substances such as fly ash and silica fume have the problem that it is difficult to obtain sufficient strength, and there is also concern that hexavalent chromium may be eluted depending on the combination with the quick-setting admixture used.
[0007] In view of the above, an object of the present invention is to provide a pozzolanic substance-containing quick-setting admixture for cement that is excellent in strength development and can suppress the elution of hexavalent chromium. [Means for solving the problem]
[0008] As a result of intensive research conducted by the present inventors in light of the above-mentioned problems, they have found that a pozzolanic substance-containing quick-setting admixture for cement containing prescribed amounts of calcium aluminate, sodium sulfate, and aluminum sulfate can solve the above-mentioned problems, and have completed the present invention.
[0009] [1] A pozzolanic substance-containing cement accelerator containing 55 to 80 mass% calcium aluminate, 3 to 25 mass% sodium sulfate, and 3 to 10 mass% or less aluminum sulfate. [2] A spraying material comprising the pozzolanic substance-containing cement quick-setting admixture described in [1] above and pozzolanic substance-containing cement. [3] The spraying material according to [2] above, wherein the pozzolan substance content in the pozzolan substance-containing cement is 30 to 90 mass%. [4] Sprayed concrete containing the spraying material described in [2] or [3] above. Effect of the Invention
[0010] According to the present invention, it is possible to provide a pozzolanic substance-containing quick-setting admixture for cement which is excellent in strength development and quick-setting properties and which can inhibit the elution of hexavalent chromium. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention (the present embodiment) will be described in detail, but the present invention is not limited to the embodiment. In addition, "%" in this specification is based on mass unless otherwise specified.
[0012] [Pozzolanic cement accelerator] The quick-setting admixture for pozzolanic substance-containing cement according to this embodiment contains 55 to 80 mass% calcium aluminate, 3 to 25 mass% sodium sulfate, and 3 to 10 mass% or less aluminum sulfate. The pozzolanic substance-containing cement in the present invention is a pozzolanic substance-containing cement obtained by mixing a pozzolanic substance such as volcanic ash or coal ash with silica cement as specified in JIS R 5212:2009 "Silica cement" or fly ash cement as specified in JIS R 5213:2009 "Fly ash cement", or ordinary Portland cement, and containing a pozzolanic substance in an amount equal to or greater than the amount specified in the above JIS.
[0013] The pozzolanic substance is a material containing a substance that exhibits a pozzolanic reaction with the hydration products of cement, and examples of such a material include fly ash, silica fume, metakaolin, volcanic ash, coal ash, diatomaceous earth, silica clay, tass, and zeolite.
[0014] The calcium aluminate contained in the pozzolan-containing cement quick-setting admixture according to this embodiment is CaO and Al 2 O 3 It is a general term for compounds that have hydration activity and are mainly composed of CaO and / or Al. 2 O 3 Compounds in which a part of the above has been replaced with alkali metal oxides, alkaline earth metal oxides, silicon oxide, titanium oxide, iron oxide, alkali metal halides, alkaline earth metal halides, alkali metal sulfates, and alkaline earth metal sulfates, etc., or CaO and Al2 O 3 It is a substance mainly composed of these and a small amount of these in solid solution, and calcium aluminate may be either crystalline or amorphous.
[0015] As a specific example of a crystalline substance, CaO is C, Al 2 O 3 A, R 2 O(Na 2 OK 2 O, Li 2 O) is R, then C 3 A and its alkali metal solid solution C 14 RA 5 , C.A., C. 12 A 7 Or C 11 A 7 ·CaF 2 , C 4 A Fe 2 O 3 , and C 3 A 3 ·CaSO 4 Among them, amorphous calcium aluminate is preferred because of its good quick setting property. In the case of amorphous calcium aluminate, the vitrification rate is preferably 80% or more.
[0016] The pozzolanic substance-containing quick-setting admixture for cement according to this embodiment contains 55 to 80 mass% calcium aluminate. If the calcium aluminate content is less than 55 mass%, strength development and quick-setting ability may not be sufficiently exhibited, and hexavalent chromium may be eluted. If it exceeds 80 mass%, strength development may not be sufficiently exhibited. The calcium aluminate content is preferably 60 to 75 mass%, more preferably 65 to 70 mass%. If the calcium aluminate content is within the above range, strength development and quick-setting ability are more easily improved, and elution of hexavalent chromium is easily suppressed.
[0017] Calcium Aluminate CaO / Al 2 O 3The molar ratio is not particularly limited, but from the viewpoints of short-term strength development and suppression of elution of hexavalent chromium, the molar ratio is preferably from 1.3 to 3.0, and more preferably from 1.6 to 2.7.
[0018] The method of obtaining calcium aluminate is to use CaO raw materials such as calcium carbonate and calcium hydroxide, and Al raw materials such as bauxite. 2 O 3 For example, the raw materials are mixed in a predetermined ratio, heated and melted in an electric furnace, and then quenched by contacting with compressed air or water. By adjusting the ratio of each raw material, the above CaO / Al 2 O 3 The molar ratio can be adjusted, and the vitrification rate can be adjusted by the temperature during heating and melting and the cooling method.
[0019] When calcium aluminate is obtained industrially, it may contain impurities. Specific examples of impurities include, for example, SiO 2 , Fe 2 O 3 , MgO, TiO 2 , MnO, Na 2 OK 2 O, Li 2 O, S, P 2 O 5 The presence of these impurities is not particularly problematic as long as it does not substantially impair the object of the present invention. Specifically, it is not particularly problematic when the total amount of these impurities is 10% or less.
[0020] The Blaine specific surface area value (Blaine value) of calcium aluminate is not particularly limited, but is usually 3,000 to 9,000 cm 2 / g is preferable, and 4,000 to 8,000 cm 2 / g is more preferable. By the Blaine value being within the above range, the handleability can be improved. The Blaine specific surface area is measured based on the specific surface area test described in JIS R 5201:2015 "Physical test method for cement".
[0021] The pozzolan substance-containing quick-setting admixture for cement according to the present embodiment contains 3 to 25% by mass of sodium sulfate. If the content of sodium sulfate is less than 3% by mass, the strength development may not be sufficiently exhibited, and if it exceeds 25% by mass, the strength development and quick-setting properties may not be sufficiently exhibited, and hexavalent chromium may be eluted. The content of sodium sulfate is preferably 5 to 20% by mass, and more preferably 10 to 15% by mass. If the content of sodium sulfate is within the above range, the strength development and quick-setting properties are more excellent, and the elution of hexavalent chromium is easily suppressed. The sodium sulfate may contain either or both of a hydrate and an anhydrate, and the content of sodium sulfate decahydrate is preferably 0 to 40% by mass.
[0022] The pozzolan substance-containing cement quick-setting admixture according to the present embodiment contains 3 to 10% by mass of aluminum sulfate. If the content of aluminum sulfate is less than 3% by mass, the strength development and quick-setting ability may not be fully exhibited, and if it exceeds 10% by mass, the strength development and quick-setting ability may not be fully exhibited, and the elution of hexavalent chromium may not be suppressed. The aluminum sulfate is preferably in the form of a powder, more preferably a 14 to 18 hydrate, and further preferably less than 50% of the particles have a particle size of 150 μm or less. The content of aluminum sulfate is preferably 3 to 8% by mass, and more preferably 4 to 6% by mass. If the content of aluminum sulfate is within the above range, the strength development and quick-setting ability are more excellent, and the elution of hexavalent chromium is more easily suppressed.
[0023] The pozzolanic substance-containing cement quick-setting admixture may contain slaked lime. The content of slaked lime is not particularly limited, but is preferably 1 to 30 mass%, and more preferably 3 to 15 mass%. When the content of slaked lime is within the above range, adhesion is improved, making it easier to suppress rebound.
[0024] The pozzolanic substance-containing cement quick-setting admixture may further contain an alkali metal salt other than the above sodium sulfate. The alkali metal salt may include silicates such as sodium silicate and potassium silicate, and carbonates such as sodium carbonate and potassium carbonate. The content of the alkali metal salt is not particularly limited, but from the viewpoint of long-term strength development and adhesion, it is preferably 0.1 to 15 mass%, more preferably 0.3 to 10 mass%.
[0025] The pozzolanic substance-containing cement quick-setting admixture may further contain an alkaline earth metal salt. The alkaline earth metal salt may include carbonates such as calcium carbonate, and sulfates such as calcium sulfate. The content of the alkaline earth metal salt is not particularly limited, but from the viewpoint of long-term strength development and adhesion, it is preferably 3 to 50 mass%, and more preferably 5 to 30 mass%.
[0026] [Spraying material] The spraying material according to the present embodiment contains the quick-setting admixture for pozzolanic substance-containing cement of the present invention and pozzolanic substance-containing cement. By containing the quick-setting admixture for pozzolanic substance-containing cement and pozzolanic substance-containing cement, the spraying material has excellent strength development and quick-setting properties and can suppress elution of hexavalent chromium.
[0027] The content of the pozzolanic cement quick-setting admixture in the spraying material is preferably 3 to 20 parts by mass, and more preferably 5 to 15 parts by mass, per 100 parts by mass of the pozzolanic cement. When the content of the pozzolanic cement quick-setting admixture is within the above range, it is easy to achieve excellent strength development and quick-setting properties, and it is easy to suppress the elution of hexavalent chromium.
[0028] The amount of the pozzolanic substance in the pozzolanic substance-containing cement is preferably 30 to 90 mass %, and more preferably 40 to 70 mass %. When the amount of the pozzolanic substance is within the above range, it is easy to suppress the elution of hexavalent chromium.
[0029] [Shocked concrete] The sprayed concrete according to the present embodiment contains the sprayed material of the present invention. The sprayed concrete can be obtained by mixing the sprayed material with water and spraying the mixture, and has excellent strength development and quick setting properties and can suppress elution of hexavalent chromium.
[0030] The content of the spraying material in the shotcrete is preferably 10 to 30 mass%, more preferably 15 to 25 mass%. When the content of the spraying material is within the above range, it is easy to achieve excellent strength development and quick setting properties, and it is easy to suppress the elution of hexavalent chromium.
[0031] The water-cement ratio of the sprayed concrete is preferably 30 to 70%, more preferably 40 to 60%, based on the pozzolanic substance-containing cement in the sprayed material. By having the water-cement ratio within the above range, it is easy to achieve excellent strength development and quick setting, and it is easy to suppress the elution of hexavalent chromium.
[0032] In practice, sprayed concrete uses aggregate, but the aggregate is not particularly limited, and preferably has low water absorption and high aggregate strength. The maximum size of the aggregate is not particularly limited as long as it can be sprayed. River sand, mountain sand, sea sand, lime sand, and silica sand can be used as fine aggregate, and river gravel, mountain gravel, and lime gravel can be used as coarse aggregate, and crushed sand and crushed stone can also be used.
[0033] The content of aggregate in the shotcrete is preferably 60 to 80 mass %, and more preferably 65 to 75 mass %. EXAMPLES
[0034] The present invention will be described in more detail below using examples and comparative examples. However, the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention.
[0035] [Experimental Example 1] <Preparation of cement accelerator containing pozzolanic substance> The materials shown below were mixed in the ratios shown in Table 1 to prepare a pozzolanic substance-containing cement quick-setting admixture.
[0036] <Materials used> Calcium aluminate: CaO / Al 2 O 3 Amorphous calcium aluminate was prepared by melting calcium carbonate and aluminum oxide in an electric furnace and quenching them so that the molar ratio was 2.3. The vitrification rate was 97% (measured by powder X-ray diffraction) and the Blaine value was 5,800 cm. 2 / g, amorphous. Sodium sulfate: anhydrous, 98% purity, industrial raw material. Aluminum sulfate: 14-18 hydrate, powder, industrial raw material. Slaked lime: purity 95%, Blaine value 5,000 cm 2 / g. Alkali metal salts: Sodium carbonate, powder, Blaine value 1,100 cm 2 / g. Alkaline earth metal salts: Anhydrous gypsum by-product, powder, Blaine value 4,500 cm 2 / g.
[0037] <Preparation of spraying materials> A pozzolanic cement-containing cement (fly ash content 50% by mass) was prepared by mixing 400 g of ordinary Portland cement (manufactured by Denka) and 400 g of fly ash (JIS Type II, industrial product) as a pozzolanic substance, and 2,000 g of fine aggregate (river sand from the Hime River system in Niigata Prefecture) and water to a water-cement ratio of 50% were added and kneaded. 10 parts by mass of the prepared pozzolanic cement quick-setting admixture was added per 100 parts by mass of the pozzolanic cement-containing cement, to prepare spraying material A.
[0038] <Coagulation test> The prepared spray material was quickly sprayed onto a formwork measuring 30 cm in length, 30 cm in width, and 10 cm in depth, and the Proctor penetration resistance was measured over time from the addition of the accelerator, reaching 3.5 N / mm 2 The time when this occurs is the starting time, 28.0N / mm 2 The time when the reaction time reached the end was determined as the termination time. The results are shown in Table 1 below.
[0039] <Compressive strength test> The prepared spray material was quickly sprayed onto a triple-section formwork measuring 4 cm length x 4 cm width x 16 cm depth, and the compressive strength was measured at 10 minutes, 30 minutes, 24 hours, and 28 days after the addition of the quick-setting admixture. The results are shown in Table 1. In the present invention, the compressive strengths at 10 minutes, 30 minutes, and 24 hours are indicators of short-term strength, and the compressive strength at 28 days is an indicator of long-term strength.
[0040] <Amount of eluted hexavalent chromium> The prepared spraying material was quickly sprayed onto the formwork after preparation, and the amount of hexavalent chromium eluted from the sprayed concrete, which had an age of 3 hours depending on the time elapsed since the addition of the accelerator, was measured based on the method specified in the "Elution Test to be carried out at the Mix Design Stage, Notification No. 46 of the Environment Agency, dated August 23, 1991. The results are shown in Table 1.
[0041] [Table 1]
[0042] [Experimental Example 2] Except for using silica fume (industrial product, granular) instead of fly ash to prepare spraying material B, each test was carried out in the same manner as in Experimental Example 1. The results are shown in Table 2.
[0043] [Table 2]
[0044] [Experimental Example 3] Using the same quick-setting admixture for pozzolanic substance-containing cement prepared as in Experimental Example 1, each test was carried out in the same manner as in Experimental Example 1, except that the amount added per 100 parts by mass of pozzolanic substance-containing cement was changed. The results are shown in Table 3.
[0045] [Table 3]
[0046] [Experimental Example 4] Each test was carried out in the same manner as in Experimental Example 1, except that the pozzolanic substance content in the pozzolanic substance-containing cement was changed using an accelerated setting admixture for pozzolanic substance-containing cement prepared in the same manner as in Experimental Example 1. The results are shown in Table 4.
[0047] [Table 4] [Industrial Applicability]
[0048] The pozzolanic substance-containing cement quick-setting admixture of the present invention can be suitably used for cement concrete to be sprayed onto exposed natural ground surfaces such as tunnels for roads, railways, and waterways, and slopes.
Claims
1. A pozzolan-containing cement quick-setting admixture containing 55 to 80 mass % calcium aluminate, 3 to 25 mass % sodium sulfate, and 3 to 10 mass % or less aluminum sulfate.
2. A spraying material comprising the pozzolanic substance-containing cement quick-setting admixture according to claim 1 and a pozzolanic substance-containing cement.
3. The spraying material according to claim 2, wherein the pozzolan substance content in the pozzolan substance-containing cement is 30 to 90 mass%.
4. A sprayed concrete comprising the spraying material according to claim 2 or 3.
Citation Information
Patent Citations
Rapidly curing agent for concrete
JP2001130935A
Liquid quick setting admixture
JP2005089276A
Liquid quick-setting agent
JP2006193388A